THE INFLUENCE OF HUMAN RESOURCE DEVELOPMENT, TRAINING, AND MANAGEMENT POLICIES ON EMPLOYEE PERFORMANCE AT PT. UNGGUL MANDIRI KENCANA - Dimas Roki Maulana; Pemilia Sulistyowati (Indo-Fintech Intellectuals: Journal of Economics and Business, 2026)
This study aims to examine the effect of human resource development, training, and management policies on employee performance at PT. Unggul Mandiri Kencana. A quantitative approach with a survey design was employed, involving a saturated sample of 32 employees. Data were analyzed using multiple linear regression. The results show that human resource development (β = 0.197; t = 1.429; p = 0.164) and training (β = 0.274; t = 1.884; p = 0.070) do not have a statistically significant effect on employee performance. In contrast, management policy has a positive and significant effect (β = 0.436; t = 3.150; p = 0.004). Simultaneously, the three independent variables significantly influence employee performance (F = 57.332; p = 0.001), with a coefficient of determination (R²) of 0.860, indicating that 86% of the variance in employee performance is explained by the model. These findings highlight that while individual competency development through HR development and training alone may not directly enhance performance, effective management policies play a critical role. The study contributes to human resource management literature by emphasizing the importance of integrating organizational policies with competency development to optimize employee performance